Effect of quercetin on steroidogenesis and folliculogenesis in ovary of mice with experimentally-induced polycystic ovarian syndrome - Shah, Mohd Zahoor ul haq; Shrivastva, Vinoy kumar; Mir, Manzoor Ahmad; Sheikh, Wajid Mohammad; Ganie, Mohd Ashraf; Rather, Gulzar Ahmed; Shafi, Majid; Bashir, Showkeen Muzamil; Ansari, Mohammad Azam; Al-Jafary, Meneerah A.; Al-Qahtani, Mohammad H.; Homeida, Abdalelgadir Musa; et al. (Frontiers in Endocrinology, 2023)
The health of many women around the world is impacted by the prevalent endocrine illness known as polycystic ovarian syndrome (PCOS). Apart from fundamental metabolic problems connected to PCOS, focus of our study is on the role of quercetin on genes relevant to steroidogenesis and folliculogenesis. Eighteen mature parkes strain mice (4-5 weeks old) weighing 18–21 g were randomly divided into three groups of six each as follows: Group I serves as the control and was given water and a regular chow diet ad lib for 66 days; group II was given oral gavage administration of letrozole (LETZ) (6 mg/kg bw) for 21 days to induce PCOS and was left untreated for 45 days; For three weeks, Group III received oral gavage dose of LETZ (6 mg/kg), after which it received Quercetin (QUER) (125 mg/kg bw orally daily) for 45 days. In our study we observed that mice with PCOS had irregular estrous cycle with decreased LH/FSH, estrogen level and decline in expression of Kitl, Bmp, Cyp11a1, Cyp19a1, Ar, lhr, Fshr and Esr1 in ovary. Moreover, we observed increase in the expression of CYP17a1, as well as increase in cholesterol, triglycerides, testosterone, vascular endothelial growth factor VEGF and insulin levels. All these changes were reversed after the administration of quercetin in PCOS mice. Quercetin treatment reversed the molecular, functional and morphological abnormalities brought on due to letrozole in pathological and physiological setting, particularly the issues of reproduction connected to PCOS. Quercetin doesn’t act locally only but it acts systematically as it works on Pituitary (LH/FSH)- Ovary (gonad hormones) axis. the Side effects of Quercetin have to be targeted in future researches. Quercetin may act as a promising candidate for medical management of human PCOS.